Work Experiences of Latina Immigrants: A Qualitative Study - Eggerth, Donald E. (J Career Dev, 2012)
Almost half of the Latino immigrants working in the United States are women. However, studies concerning the work experiences of Latinas are almost absent in the literature. This article reports the findings from a qualitative study using eight focus groups (n = 53) of Latina immigrant workers. The focus group transcripts were analyzed using the grounded theory approach in which themes emerge from iterative readings of the transcripts by a group of investigators. This study identified themes related to excessive workload, familiar work/unfamiliar hazards, cultural tensions, lack of health care, pregnancy, sexual harassment, and family obligations/expectations. The responses of the Latina workers in this study clearly indicated that they live within a complex web of stressors, both as workers and as women. The increased economic opportunities that come with immigration to the United States are accompanied by many opportunities for exploitation, especially if they are undocumented. It is hoped that the findings of this study will raise awareness regarding these issues and spur further work in this area.